Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÑÐ¾Ñ…Ñ€Ð°Ð½ÐµÐ½Ð¸Ñ Ð°Ñ€Ñ…Ð¸Ñ‚ÐµÐºÑ‚Ð¾Ð½Ð¸ÐºÐ¸ Ñ‚ÐºÐ°Ð½Ð¸ Ð½Ð° ÐºÑ€Ð¸Ð¾Ñ‡ÑƒÐ²ÑÑ‚Ð²Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ð¾ÑÑ‚ÑŒ Ð½Ð°Ð´Ð¿Ð¾Ñ‡ÐµÑ‡Ð½Ñ‹Ñ… Ð¶ÐµÐ»ÐµÐ· Ð¼Ñ‹ÑˆÐµÐ¹ Ð¸ Ð½Ð¾Ð²Ð¾Ñ€Ð¾Ð¶Ð´ÐµÐ½Ð½Ñ‹Ñ… Ð¿Ð¾Ñ€Ð¾ÑÑÑ‚ - Ustichenko, V. D.; Alabedalkarim, N. M.; Bondarenko, T. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
We investigated the influence of keeping the histological architecture on the cryosensitivity of single cells suspension and fragments of mice and newborn piglets’ adrenal glands. It was shown that the adrenal gland fragments were more resistant to effect of low temperature preservation factors, comparing to single adrenocortical cells, and as a result, had both basal and stimulated steroidogenesis. The highest diffusion barrier in fragments changes their sensitivity to effect of stimulators, efficient at the interaction with intracellular targets, but doesn’t influence the regulation, which are realized due binding with receptors, dirrected to the cell outside.